2022
DOI: 10.3390/antibiotics12010037
|View full text |Cite
|
Sign up to set email alerts
|

High Occurrence of Multidrug-Resistant Escherichia coli Strains in Bovine Fecal Samples from Healthy Cows Serves as Rich Reservoir for AMR Transmission

Abstract: Objectives: Antibiotics are valuable therapeutics. However, the unwarranted and excessive use of these antimicrobials in food animals and the consequent contamination of the environment have been associated with the emergence and spread of antimicrobial resistance. Continuous surveillance and monitoring of antimicrobial resistance among E. coli isolates is recommended, not only for bovine health but also for public health. This study aims to assess the antimicrobial resistance profile, virulence potential, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…and both the MAR index and R-score, speculating the significant clinical concern for these resistance patterns. These findings align with the results of a study conducted by Jalil et al [54], where similar trends of higher MAR index and R-score in E. coli isolates were reported. Our finding is consistent with other studies on bacteria of marine bivalves conducted in different parts of Korea [17,32,35,55] with a higher MAR index in Aeromonas spp.…”
Section: Discussionsupporting
confidence: 93%
“…and both the MAR index and R-score, speculating the significant clinical concern for these resistance patterns. These findings align with the results of a study conducted by Jalil et al [54], where similar trends of higher MAR index and R-score in E. coli isolates were reported. Our finding is consistent with other studies on bacteria of marine bivalves conducted in different parts of Korea [17,32,35,55] with a higher MAR index in Aeromonas spp.…”
Section: Discussionsupporting
confidence: 93%
“…E. coli is an interesting study model given its omnipresence in nature as a commensal and pathogen, being one of the primary vehicles that can transmit resistance and virulence genes between different species [ 15 ]. The monitoring of antibiotic-resistant E. coli strains from food animals and products is vital to determine its potential risk to humans [ 16 ]. This study found that 5.0% of strains recovered from livestock samples (cattle, pigs, chickens and sheep) were ESBL-EC.…”
Section: Discussionmentioning
confidence: 99%
“…The health risk associated with the spread of antibiotic resistance in the environment is estimated using the multiple antibiotic resistance index (MARI) [ 16 , 30 ]. In this study, all of the values obtained show that the MARI was greater than 0.2, suggesting that the ESBL-EC strains originated from an environment with a high contamination or overuse of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations